Optical follow-up of the tick-tock massive black hole binary candidate. Issue 3 (17th November 2022) - Dotti, Massimo; Bonetti, Matteo; Rigamonti, Fabio; Bortolas, Elisa; Fossati, Matteo; Decarli, Roberto; Covino, Stefano; Lupi, Alessandro; Franchini, Alessia; Sesana, Alberto; Calderone, Giorgio
ABSTRACT: The observation of a population of massive black hole binaries (MBHBs) is key for our complete understanding of galaxy mergers and for the characterization of the expected gravitational waves (GWs) signal. However, MBHBs still remain elusive with only a few candidates proposed to date. Among these, SDSSJ143016.05 + 230344.4 ('tick-tock' hereafter) is the only candidate with a remarkably well sampled light curve showing a clear reduction of the modulation period and amplitude over three years of observations. This particular feature has been recently claimed to be the signature of a MBHB that is about to merge. In this paper, we provide an optical follow-up of the tick-tock source using the Rapid Eye Mount (REM) telescope. The decreasing luminosity observed in our follow up is hardly explained within the binary scenario. We speculate about an alternative scenario that might explain the observed light curve through relativistic Lense-Thirring precession of an accretion disc around a single massive black hole.